2011
DOI: 10.5130/ajceb.v11i3.2134
|View full text |Cite
|
Sign up to set email alerts
|

Work Stress among Professionals in Building Construction Industry in Nigeria

Abstract: This study was undertaken to identify key stress factors among professionals in the building construction industry in Nigeria. This is in view of the fact that to date, very little is known about work stress among professionals in the building construction industry in this country. The study involved the administration of a questionnaire to 107 professionals including architects, builders, civil/structural engineers and quantity surveyors randomly selected from 60 ongoing building projects in Anambra, Ogun and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 20 publications
8
73
2
Order By: Relevance
“…However, contrary to our findings, a higher percentage of "extreme high strain" workers were reported by Khagendra and Rachna [17] and Gaurav et al [5] In another similar study done by Tiwary et al, [6] 60% of the workers in the study experienced psychological stress and strain. Ibem et al [18] reported lower rates of psychological strain and stress as compared to this study. The difference may be due to different geographical settings.…”
Section: Discussioncontrasting
confidence: 50%
“…However, contrary to our findings, a higher percentage of "extreme high strain" workers were reported by Khagendra and Rachna [17] and Gaurav et al [5] In another similar study done by Tiwary et al, [6] 60% of the workers in the study experienced psychological stress and strain. Ibem et al [18] reported lower rates of psychological strain and stress as compared to this study. The difference may be due to different geographical settings.…”
Section: Discussioncontrasting
confidence: 50%
“…Larsson et al, 2008;Bowen et al, 2014;Rowlinson et al, 2014) and hard manual activities (e.g. Dembe et al, 2005;Ibem et al, 2011;Chan, Leung & Yuan, 2014). The great majority of studies that have investigated the nature of stress among construction workers have been predominantly quantitative.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous research has been conducted regarding stress confronting construction professionals like: (Bowen et al 2013;Cattell et al 2016;Ibem et al 2011;Leung et al 2017). However, those studies have failed to appraise the strategies adopted by construction professionals for coping with stress.…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al (2017) affirmed that stress is not attributed to a particular industry although the construction industry has a reputation for being a stressful industry. Ibem et al (2011) opined that the stress experienced in the construction industry originates from the working condition of the industry. Likewise, Leung et al (2017) recognised that the construction industry production process is the primary source of stress confronting construction workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation